2017
DOI: 10.12688/f1000research.12539.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive-behavioral counseling on anxiety in the mothers of infants in the NICU:  A randomized controlled trial

Abstract: Background: Pressures and tensions in everyone’s life can cause a wide range of mental disorders such as anxiety. One of these tensions is the birth of a baby who requires special care, which can cause personal and social problems for the mother if no appropriate measures are taken to help them. The present study was conducted to determine the effect of cognitive-behavioral counseling on anxiety in the mothers of infants in the Neonatal Intensive Care Unit. Methods: This randomized controlled trial recruited 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The data findings in Table 3 presented the posttest level of anxiety score among mothers of preemies between the experimental and control groups. The base line anxiety score in the pre-test was 41.22 and the post-test anxiety score was 25.45 after the intervention and mean difference in anxiety score was 15.77 in the experimental group shows highly significant at P≤0.01, very highly significant at P≤0.001 The present study findings were found to be consistent with the research findings put forward by Koochaki M, et al [15] found that the anxiety score before the intervention was 19.45 and reduced to 11.52 after the intervention in experimental group. Whereas, in the control group, the pre-test score was 20.67 and reduced to 8.95 in the post test.…”
Section: Discussionsupporting
confidence: 91%
“…The data findings in Table 3 presented the posttest level of anxiety score among mothers of preemies between the experimental and control groups. The base line anxiety score in the pre-test was 41.22 and the post-test anxiety score was 25.45 after the intervention and mean difference in anxiety score was 15.77 in the experimental group shows highly significant at P≤0.01, very highly significant at P≤0.001 The present study findings were found to be consistent with the research findings put forward by Koochaki M, et al [15] found that the anxiety score before the intervention was 19.45 and reduced to 11.52 after the intervention in experimental group. Whereas, in the control group, the pre-test score was 20.67 and reduced to 8.95 in the post test.…”
Section: Discussionsupporting
confidence: 91%
“…A systematic review of studies of interventions for perinatal anxiety disorders similarly highlighted the limited data (and high levels of heterogeneity), but found evidence of significant reductions in anxiety symptom severity with interventions also used at other times in a woman's life 89 . There is also some evidence from small trials suggesting that CBT can reduce symptoms in women with blood and injection phobias in pregnancy 90 , PTSD and depression in mothers who have babies on a neonatal intensive care unit 91,92 , and postnatal OCD 93 .…”
Section: Interventionsmentioning
confidence: 99%
“…Selected studies included seven randomized controlled trials (RCTs) (Dabas et al, 2019;Jouybari et al, 2018;Koochaki et al, 2017;Kucuk Alemdar et al, 2018;Petteys & Adoumie., 2018;Ribeiro et al, 2018;Welch et al, 2016) and seven quasi-experimental designs (Akbari et al, 2019;Gustafson et al, 2016;John et al, 2018;Kadivar et al, 2016;Mansson et al, 2019;Noergaard et al, 2018;Ong et al, 2018). One of the RCT studies was blinded (Jouybari et al, 2018).…”
Section: Methodsmentioning
confidence: 99%